Terrestrial biosphere changes over the last 120 kyr - Hoogakker,BAA; Smith,RS; Singarayer,JS; Marchant,R; Prentice,IC; Allen,JRM; Anderson,RS; Bhagwat,SA; Behling,H; Borisova,O; Bush,M; Correa-Metrio,A; et al. (Climate of the Past, 2016)
A new global synthesis and biomization of long (>40kyr) pollen-data records is presented and used with simulations from the HadCM3 and FAMOUS climate models and the BIOME4 vegetation model to analyse the dynamics of the global terrestrial biosphere and carbon storage over the last glacial–interglacial cycle. Simulated biome distributions using BIOME4 driven by HadCM3 and FAMOUS at the global scale over time generally agree well with those inferred from pollen data. Global average areas of grassland and dry shrubland, desert, and tundra biomes show large-scale increases during the Last Glacial Maximum, between ca. 64 and 74ka BP and cool substages of Marine Isotope Stage 5, at the expense of the tropical forest, warm-temperate forest, and temperate forest biomes. These changes are reflected in BIOME4 simulations of global net primary productivity, showing good agreement between the two models. Such changes are likely to affect terrestrial carbon storage, which in turn influences the stable carbon isotopic composition of seawater as terrestrial carbon is depleted in 13C.